Agronegócio cercando agroecologia : modo de vida e conflito sócio-ambiental em comunidades agrícolas de Tabuleiro de Russas, Ceará. - Braga, Lara de Queiroz Viana (2010)
The purpose of this research is to understand how the agricultural communities of Lagoa dos Cavalos, Junco, Barbatão and Córrego Salgado, in the municipality of Russas, state of Ceará, Brazil, have created alternatives to development in defense of their way of life and as a strategy of resistance to the expanding large-scale agribusiness at the sub-basin of the Lower Jaguaribe River. Our reference framework draws from the analytic categories of “ideology of development” (Rigotto, 2008), “alternatives to development” (Santos, 2005), “agroecology” (Altieri, 2009) and “socio-environmental conflict” (Acselrad, 2004). The methodological approach is based on the depth hermeneutics of Thompson (1996), reaching over the ethnographic methods of participant observation (Malinowsky, 1984) and thick description (Geertz, 1989). As results of the description of the traditional agricultural life of the communities of Lagoa dos Cavalos, Junco, Barbatão and Córrego Salgado, we reveal the social and historical process in the creation of alternatives of coexistence with the semi-arid climate, characterizing the agricultural biodiversity and its interrelation with the work processes of family-based agriculture and beekeeping, along with the potential for communitorganization; and the process of agroecological transition in the promotion of health in the countryside. Regarding the characterization of the socio-environmental conflict between the agricultural communities and the National Department of Public Works against Drought (in the Brazilian acronym, DNOCS), we unveil the threads of the tension between the production model of agribusiness and the agricultural ways of life in the dry countryside of the state of Ceará; the limitations of the instruments for evaluating environmental impacts; the local movement of resistance; and the construction of territorial alternatives as a counterproposal to the original project laid down by the federal government. Based on an empirical work, this descriptive-documental study dwells with the linkages between health, environment and production, and presents some reflections on the endogenous potential of the communities in the construction and effective execution of the public policies of rural development and promotion of health in the countryside.